Self-reported pain assessment, core competence and practice ability for palliative care among Chinese oncology nurses: a multicenter cross-sectional study - Jia Jia; Fan Fan Lv; Zhen Hua Cai; Long Ti Li; Xiao Fei Nie (BMC Nursing, 2024)
Abstract Objective The study was to survey the current situation and explore the relationship between pain assessment ability, palliative care core competence and palliative care practice ability among oncology nurses in mainland China. Methods A multicenter cross-sectional study design was employed. Study data were collected in 26 tertiary hospitals among 1198 registered oncology nurses in the oncology department in Hubei province, China. A web-based survey was conducted using a stratified random integral sampling method to obtain data. All variables were measured using standardized instruments. Data was analyzed using SPSS 26.0 and AMOS 26.0 statistical software. All statistical tests were two-sided, with the significance level set at P < 0.05. The structural equation model was utilized to test the mediation effect of pain assessment ability on the pathway from palliative care core competence to palliative care practice ability. Results The mean scores for pain assessment, core competence and practice ability were 125.68 (SD = 31.16), 76.67 (SD = 19.59) and 67.17(SD = 12.57), respectively. Pearson correlation analysis revealed significant positive correlations among the PCPS, EPCS, and Self-PAC scores of the oncology nurses (P < 0.01). The association between core competence and palliative care practice ability was mediated by pain assessment ability (ES = 0.125, 95%CI: 0.090–0.168). Conclusions To enhance the effectiveness of palliative care practice, managers need to strengthen the core competencies of palliative care nurses and their ability to assess patients’ pain, as these two factors will promote the practical abilities of oncology nurses.